2017
DOI: 10.1515/jppr-2017-0035
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of three species of the genus Oscheius Andrássy, 1976 (Nematoda: Rhabditida) in Iran

Abstract: Due to importance and effectiveness of some entomopathogenic or insect parasitic nematodes in controlling of agricultural pests, or pests of non-agricultural plants, a study was conducted in order to identify the species of this group of nematodes in city of Tehran. As the result, three species belonging to the genus Oscheius were recovered in association with bark samples having the bark beetle galleries. Morphological and molecular data were provided for two recently recovered species of the genus, namely O.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Morphometrically, the also show close similitude to each other, such as in the size of the females; similar ratios (a, b, c, and c’); similar anal body width; similar SW%, GS% and V%; and other morphometric measurements ( Supplementary Tables S2 and S3 ). Therefore, O. rugaoensis is proposed as a junior synonym of O. chongmingensis , while the population from Japan [ 50 ] attributed to O. rugaoensis should be considered conspecific with the population of O. necromenus that is described from Iran [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Morphometrically, the also show close similitude to each other, such as in the size of the females; similar ratios (a, b, c, and c’); similar anal body width; similar SW%, GS% and V%; and other morphometric measurements ( Supplementary Tables S2 and S3 ). Therefore, O. rugaoensis is proposed as a junior synonym of O. chongmingensis , while the population from Japan [ 50 ] attributed to O. rugaoensis should be considered conspecific with the population of O. necromenus that is described from Iran [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oscheuis rugaoensis was reported from Iran, isolated from the white grub larvae Polyphylla adspersa Motschulsky, 1853 (Coleopera: Scarabaeidae) ( Darsouei et al, 2014 ). Valizadeh et al (2017) recovered three species O. necromenus ( Sudhaus and Schulte, 1989 ), O. onirici Torrini et al, 2015 and O. tipulae in association with bark beetle galleries in Tehran, Iran. The application of native EPNs is preferred for more successful and environmental low-risk purposes ( Labaude and Griffin, 2018 ).…”
mentioning
confidence: 99%
“…Hassani-Kakhki et al (2012) reported O. tipulae (Lam and Webster, 1971) from Iran in the shape of an abstract. Oscheuis rugaoensis was reported from Iran, isolated from the white grub larvae Polyphylla ads persa (Motschulsky, 1853) (Coleopera: Scarabaeidae) (Darsouei et al, 2014). Valizadeh et al (2017 recovered three species O. necromenus (Sudhaus and Schulte, 1989), O. onirici (Torrini et al, 2015) and O. tipulae in association with bark beetle galleries in Tehran, Iran.…”
mentioning
confidence: 99%
“…Another species, Heterorhabditidoides rugaoensis, was also transferred to Oscheius (Darsouei et al, 2014;Tabassum et al, 2016). Synonymizing Heterorhabditoides with Oscheius has been widely accepted in the field (Liu et al, 2012;Campos-Herrera et al, 2015;Torrini et al, 2015;Tabassum et al, 2016;Valizadeh et al, 2017). A total of 44 species of Oscheius have been described till date, out of which 16 are from the Indian sub-continent.…”
mentioning
confidence: 99%